Development of molecularly targeted agents and immunotherapies in small cell lung cancer. (June 2016) - Sharp, Adam; Bhosle, Jaishree; Abdelraouf, Fatma; Popat, Sanjay; O'Brien, Mary; Yap, Timothy A.
Abstract: Small cell lung cancer (SCLC) is a smoking-induced malignancy with multiple toxin-associated mutations, which accounts for 15% of all lung cancers. It remains a clinical challenge with a rapid doubling time, early dissemination and poor prognosis. Despite multiple clinical trials in SCLC, platinum-based chemotherapy remains the mainstay of treatment in the first line advanced disease setting; good initial responses are nevertheless inevitably followed by disease relapse and survival ultimately remains poor. There are currently no molecularly targeted agents licenced for use in SCLC. Advances in sequencing the cancer genome and other high-throughput profiling technologies have identified aberrant pathways and mechanisms implicated in SCLC development and progression. Novel anti-tumour therapeutics that impact these putative targets are now being developed and investigated in SCLC. In this review, we discuss novel anti-tumour agents assessed in SCLC with reference to the complex molecular mechanisms implicated in SCLC development and progression. We focus on novel DNA damage response inhibitors, immune checkpoint modulators and antibody-drug conjugates that have shown promise in SCLC, and which may potentially transform treatment strategies in this disease. Finally, we envision the future management of SCLC and propose a biomarker-driven translational treatment paradigm for SCLC that incorporates next generation sequencing studies with patient tumours, circulating plasma DNA and functional imaging. Such modern strategies have the potential to transform the management and improve patient outcomes in SCLC. Highlights: Small cell lung cancer (SCLC) is a smoking-induced malignancy that accounts for 15% of all lung cancers. No molecularly targeted agents are licenced for use in SCLC. Sequencing the cancer genome has identified aberrant pathways implicated in the pathogenesis of SCLC. DNA damage response inhibitors, immune checkpoint modulators and antibody-drug conjugates (ADCs) show promise in SCLC. Biomarker-driven treatment strategies for SCLC have the potential to improve patient outcomes.